Normalized Apparent Diffusion Coefficient in the Prognostication of Patients with Glioblastoma Multiforme. (20th January 2016) - Shankar, Jai Jai Shiva; Bata, Adil; Ritchie, Krista; Hebb, Andrea; Walling, Simon
Abstract: Background: Glioblastoma multiforme (GBM) is known to have poor prognosis, with no available imaging marker that can predict survival at the time of diagnosis. Diffusion weighted images are used in characterisation of cellularity and necrosis of GBM. The purpose of this study was to assess whether pattern or degree of diffusion restriction could help in the prognostication of patients with GBM. Material and Methods: We retrospectively analyzed 84 consecutive patients with confirmed GBM on biopsy or resection. The study was approved by the institutional ethics committee. The total volume of the tumor and total volume of tumor showing restricted diffusion were calculated. The lowest Apparent Diffusion Coefficient (ADC) in the region of the tumor and in the contralateral Normal Appearing White Matter were calculated in order to calculate the nADC. Treatment and follow-up data in these patients were recorded. Multivariate analsysis was completed to determine significant correlations between different variables and the survival of these patients. Results: Patient survival was significantly related to the age of the patient (p<0.0001; 95% CI-1.022-1.043) and the nADC value (p=0.014; 95% CI-0.269-0.860) in the tumor. The correlation coefficients of age and nADC with survival were −0.335 (p=0.002) and 0.390 (p<0.001), respectively. Kaplan Meier survival function, grouped by normalized Apparent Diffusion Coefficient cut off value of 0.75, was significant (p=0.007). Conclusion: The survival of patients with GBM had small, but significant, correlations with the patient's age and nADC within the tumor. RÉSUMÉ: Coefficient de diffusion apparent normalisé pour le pronostic de patients atteints de glioblastome multiforme. Contexte: Il est bien connu que le pronostic du glioblastome multiforme (GBM) est sombre, sans qu'il y ait de marqueur disponible à l'imagerie qui puisse prédire la survie du patient au moment du diagnostic. Les images pondérées en diffusion sont utilisées pour caractériser la cellularité et la nécrose d'un GBM. Le but de cette étude était d'évaluer si l'aspect ou le degré de restriction de la diffusion pourrait aider à établir le pronostic chez les patients atteints d'un GBM. Méthode: Nous avons analysé rétrospectivement les données de 84 patients consécutifs chez qui le diagnostic de GBM a été confirmé par biopsie ou résection. L'étude a été approuvée par le comité d'éthique de l'institution. Nous avons calculé le volume total de la tumeur et le volume total de la tumeur montrant une restriction de la diffusion. Nous avons calculé le coefficient de diffusion apparent (ADC) le plus bas dans la région de la tumeur et dans la substance blanche d'apparence normale afin de calculer l'ADC normalisé (ADCn). Nous avons noté les informations sur le traitement et le suivi de ces patients. Nous avons utilisé une analyse multivariée pour déterminer s'il existait des corrélations significatives entre les différentes variables et la survie de ces patients. Résultats: La survie des patients était reliée de façon significative à l'âge du patient (p<0, 0001 ; IC à 95% : 1, 022 à 1, 043) et à la valeur de l'ADCn (p=0, 014 ; IC à 95% : -0, 269 à -0, 860) dans la tumeur. Les coefficients de corrélation de l'âge et de l'ADCn à la survie étaient de -0, 335 (p=0, 002) et 0, 390 (p<0, 001) respectivement. L'estimateur de Kaplan-Meier de la fonction de survie groupée par ADCn utilisant une valeur limite de 0, 75 était significative au point de vue statistique (p=0, 007). Conclusion: La survie des patients atteints d'un GBM avait une corrélation faible mais significative avec l'âge du patient et avec l'ADCn à l'intérieur la tumeur.